Deadly cultures : biological weapons since 1945 - Wheelis, Mark; Rózsa, Lajos, 1961-; Dando, Malcolm (Harvard University Press, 2006)
The threat of biological weapons has never attracted as much public attention as in the past five years. Yet there has been little historical analysis of such weapons over the past half-century. Deadly Cultures sets out to fill this gap by analyzing the historical developments since 1945 and addressing three central issues: why states have continued or begun programs for acquiring biological weapons, why states have terminated biological weapons programs, and how states have demonstrated that they have truly terminated their biological weapons programs.